ISLAMIC ENTREPRENEURSHIP IMPLEMENTATION IN MUSLIM FAMILY BUSINESS (Case Study of PT Ma’soem Employees) - Faidh Rahmani Nasr; Juliana Juliana; B. Lena Nuryanti (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2021)
One of the factors affecting the economy today is a family company. More than 95% of businesses in Indonesia are family owned. 85% of the majority Muslim population should be controlled by Muslims, but in fact 35% of non-Muslims can control the Indonesian economy, from trade to manufacturing. This study aims to determine how the implementation of Islamic entrepreneurship at PT Ma’soem. This research uses descriptive quantitative methods, the population is PT Ma’soem employees, with a sample of 100 people with non-probability sampling techniques. The instrument in this study used a questionnaire. The results of the study show that the implementation of Islamic entrepreneurship in a very good category is based on three diluted variables, namely the characteristics of Islamic entrepreneurship, the nature of Islamic entrepreneurship and aspects of blessing. Overall, the lowest dimension in getting an assessment is the nature of Islamic entrepreneurship, Islam has its own entrepreneurial characteristics and guiding principles based on the Qur'an and hadith to guide entrepreneurial activities, which will have implications for the index for success in entrepreneurship and the above variables direct Muslim entrepreneurs to conduct their business activities based on the Qur'an and Hadith, this company has carried out the principles of Islamic entrepreneurship well but still has to pay more attention to employees in accordance with sharia, and the lack of reading the verses of the Koran in the office.Hadith so that this company must pay more attention to the company in accordance with sharia, and even more playing Qur-an in the office.